Foreign direct investments, trade openness and CO2 emissions relationship: the case of 1995-2019 EU countries (Revista de Investigaciones Universidad del Quindío, 2021)
Foreign direct investments (FDI), which are very important in the economic development of countries, prefer regions with free trade. Since the share of international trade in the world economy is constantly increasing, trade openness and foreign direct investments have become more important for countries. However, the increase in trade and FDI entries can have negative effects on the environment. Although many different variables are included in the literature as determinants of carbon emission, foreign direct investments are mostly taken as an explanatory variable with the effect of the economic globalization process. The aim of this paper is to analyze the relationship between FDI, trade openness and CO2 emission for the 1995-2019 period in 24 EU countries. The relationship between variables was estimated by applying panel AMG estimator and Emirmahmutoglu and Kose causality tests to series with cross-sectional dependency. Empirical results for the overall panel show that there is unidirectional causality from carbon emission to trade openness and FDI. There is a directional causality from FDI to trade openness for the general panel has been determined.     When analyzed on a country basis, there is unidirectional causality from carbon emission to trade openness for Bulgaria, Italy, Latvia, Poland, Portugal and Slovenia. Likewise, for Austria, Denmark, Estonia, Finland, France, Germany, Poland, Portugal, Spain and Switzerland, there is unidirectional causality from carbon emission to FDI. In addition, when analyzed on a country basis, there is a one-way causality relationship from foreign direct investments to trade openness for Bulgaria, Italia, Latvia, Poland, Portugal and Slovenia. For Bulgaria, Finland and Germany, there is a one-way causality from trade openness to foreign direct investment.  The importance of this study derives from the emphasis on the need for environmentally protective FDIs to reduce carbon emissions.
Keywords: Carbon emission; foreign direct investment (FDI); trade openness; environmental Kuznets curve; pollution haven hypothesis; halo effect